A companion to the era of Andrew Jackson - Adams, Sean P. (New York : Blackwell Pub., 2013)
A Companion to the Era of Andrew Jackson offers a wealth of new insights on the era of Andrew Jackson. This collection of essays by leading scholars and historians considers various aspects of the life, times, and legacy of the seventh president of the United States. Provides an overview of Andrew Jackson's life and legacy, grounded in the latest scholarship and including original research spread across a number of thematic areasFeatures 30 essays contributed by leading scholars and historiansSynthesizes the most up-to-date scholarship on the political, economic, social.
pt. I. Young Andrew Jackson's America -- pt. II. The era of the "Common Man" -- pt. III. Politics in the age of Jackson -- pt. IV. Jacksonian legacies.
Includes bibliographical references and index.
Online resource; title from pdf information screen (Ebsco, viewed February 5, 2013).
Keywords: Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845.; Presidents -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- 19th Century; Presidents; United States; Electronic books; Biography